Study of Prolonged Bearing Strength of Frozen Soils Under Uniaxial Compression - Shusherina,E. P.; Vyalov,S. S. (1965)
The report contains experimental studies on uniaxial compression of frozen grounds when creep is present. In the study of creep and strength of frozen grounds in the case of uniaxial compression the following were the principal problems considered: (a) clarification of the character of the creep curves in the case of constant stress; (b) determination of the dependence between time before destruction and stress (the pattern of decrease of strength with time); (c) clarification of the dependence between deformation and stress with the influence of time taken into account. The object of investigation was two grounds with strata situated over an ore body -- Callovian sandy loam and Bathonian-Bajocian clay, belonging to Jurassic deposits and constituting the most dangerous horizons for the penetration of drifts. (Author) Trans. of mono. Merzlotnye Issledovaniya (Geocryology Research), Moscow, 1963 p314-347.